Effectiveness of Teaching Practice Supervision as Perceived by Student-Teachers in Ilorin Metropolis, Nigeria - Yusuf, Hamdallat Taiwo; Odutayo, Adesegun Olayide; Tuoyo, Anino Omawunmi (FKIP - Universitas Riau, 2022)
Teaching practice is central to achieving the goals of teacher education. It provides student-teachers needed experience in real teaching and learning environment. This study examined student-teachers perception of the effectiveness of teaching practice supervision. The quantitative descriptive method was employed to conduct the study. Random sampling technique was employed to sample 150 student-teachers at the 400 level of a university in the metropolis. A researchers-designed questionnaire titled “Student-teachers’ Perception of the Effectiveness of Teaching Practice Supervision Questionnaire (STPETPSQ)” was used for data collection, with descriptive and inferential statistics used for data analysis. Findings revealed that the majority of the student-teachers perceived teaching practice supervision as effective for improving students’ teaching knowledge and skills. There was no significant difference was established in the perception of student-teachers on the basis of departments. It was recommended that teaching practice supervision should be improved upon to assist student-teachers to adopt appropriate and varied teaching methods.